Metabolic, inflammatory and adipokine differences on overweight/obese children with and without metabolic syndrome: a cross-sectional study - Bello Chavolla, Omar Yaxmehen; Cura Esquivel, Idalia; Perales Quintana, Marlene Marisol; Torres González, Liliana; Guzmán Avilán, Katia; Muñoz Espinosa, Linda Elsa; Cordero Pérez, Paula (PLOS ONE, 2023)
Background